LB02.02: EFFECT OF ARTERIOVENOUS ANASTOMOSIS ON BLOOD PRESSURE REDUCTION IN PATIENTS WITH ISOLATED SYSTOLIC HYPERTENSION COMPARED TO COMBINED HYPERTENSION. (June 2015) - Schmieder, R.E.; Ott, C.; Lobo, M.D.; Sobotka, P.A.; Mahfoud, F.
Abstract : Objective: Several interventional therapeutic options for blood pressure (BP) lowering in patients with treatment-resistant hypertension (TRH) were introduced, such as renal denervation (RDN) and creation of an arteriovenous (AV) anastomosis using the ROX coupler. It was shown that BP response after RDN is greater in patients with combined hypertension (CH) compared to patients with isolated systolic hypertension (ISH). We analyzed now the effect of ROX coupler implantation in the subgroups with CH and ISH. Design and method: The randomized, controlled, ROX CONTROL HTN study included patients with true TRH (office systolic BP >=140mmHg, and average daytime ambulatory BP >=135/85mmHg, despite treatment with at least 3 antihypertensive drugs including a diuretic). In our post-hoc analysis we have stratified the patients of the ROX coupler group (n = 42) according CH (n = 31) versus ISH (n = 11). Results: Baseline systolic office (177 ± 18 versus 169 ± 17 mmHg, p = 0.163) and ambulatory BP (159 ± 16 versus 154 ± 11 mmHg, p = 0.463) did not differ between CH and ISH. Creation of an AV anastomosis resulted in a significant reduction in systolic office (CH: −28 ± 22 versus ISH: −22 ± 31 mmHg, p = 0.572) as well as ambulatory BP (CH: −14 ± 20 versus ISH: −13 ± 15 mmHg, p = 0.672), but without significant differences between the two subgroups. The non-responder rate (systolic office BP reduction < 10 mmHg) after 6 months was not different between the subgroups (CH: 18 % versus ISH: 23 %, p = 0.844). Conclusions: Thus, our data suggest that creation of an AV anastomosis using the ROX coupler reduces systolic office and ambulatory BP, without any significant difference between CH and ISH. In contrast to RDN, creation of an AV anastomosis reduced BP to similar extent in both subtypes of TRH.